2018
DOI: 10.1038/s41389-018-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

RecQL4-Aurora B kinase axis is essential for cellular proliferation, cell cycle progression, and mitotic integrity

Abstract: Human RecQL4 helicase plays critical roles in the maintenance of genomic stability. Mutations in RecQL4 helicase results in three clinically related autosomal recessive disorders: Rothmund–Thomson syndrome (RTS), RAPADILINO, and Baller–Gerold syndrome. In addition to several premature aging features, RTS patients are characterized by aneuploidy involving either loss or gain of a single chromosome. Chromosome mosaicism and isochromosomes involving chromosomes 2, 7, and 8 have been reported in RecQL4-deficient R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…These kinases participate in regulating genomic stability, mitosis, and the cell cycle. 21,22 V$E2F1_Q6 and V$E2F1_Q4, the most significant transcription factors that were shown to be associated with LMNB2, belong to the E2F1 family. Numerous studies have reported the promoting effect of E2F1 on multiple cancers, including HCC, and that a high level of E2F1 is correlated with poor HCC survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinases participate in regulating genomic stability, mitosis, and the cell cycle. 21,22 V$E2F1_Q6 and V$E2F1_Q4, the most significant transcription factors that were shown to be associated with LMNB2, belong to the E2F1 family. Numerous studies have reported the promoting effect of E2F1 on multiple cancers, including HCC, and that a high level of E2F1 is correlated with poor HCC survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The kinases‐target gene set enrichment analysis of the LMNB2 network system revealed that kinase gene sets (kinase_CDK1, kinase_PLK1, kinase_CDK2, kinase_ATM, and kinase_AURKB) were significantly correlated with LMNB2. These kinases participate in regulating genomic stability, mitosis, and the cell cycle 21,22 . V$E2F1_Q6 and V$E2F1_Q4, the most significant transcription factors that were shown to be associated with LMNB2, belong to the E2F1 family.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the highly ANLN-related kinases studied in this study, PLK1, which belongs to the conserved serine/threonine kinases family involved in multiple mitotic processes (including functional maturation of centrosomes and response to DNA damage), is emphasized by previous literature to be a determinant factor of the SN38 sensitivity of tumor cells, and its over-expression is inversely correlated with the survival rate of HCC [14][15][16]. Other kinases, such as CDK1 and AURKB involved in our analysis, also regulate the genomic stability, mitosis and cell cycle [17,18]. In terms of the TFs targeted by ANLN, E2F1 is one of the key links in the cell cycle regulation network, and its aberrant expression is actively involved in HCC genesis and development of HCC, which predicts the unfavorable prognosis for patients [19,20].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, among the highly NEIL3-related kinases investigated in this study, PLK1, one of the conserved serine/threonine kinase family members involved in multiple mitotic processes (including functional maturation of centrosomes, establishment of the bipolar spindle, chromosome segregation and response to DNA damage), was suggested in previous study to be a factor that determined the SN38 sensitivity of tumor cells, and its over-expression was inversely correlated with the survival rate of HCC [39]. Besides, other kinases, such as CDK1 and AURKB, which are involved in our network, also regulate genomic stability, mitosis and the cell cycle [40,41]. Among the TFs targeted by NEIL3, E2F1 represents a key link in the cell cycle regulation network, and its aberrant expression participates in HCC occurrence and development, which also predicts the unfavorable patient prognosis [42].…”
Section: Discussionmentioning
confidence: 95%